Implikasi Teologi Sosial dalam Kehidupan Bermasyarakat - Komang Heriyanti; Ni Made Evi Kurnia Dewi (Sphatika: Jurnal Teologi, 2020)
Social life is influenced by many worldly objects. For that we need a norm that regulates social life. In this case the role of religious norms is to teach humanity to respect others. The presence of social theology becomes a norm and value in individuals which will be a framework for attitude and behavior in social life to be in accordance with the teachings of the religion they hold. Religious teachings as regulators of life and life in society are automatically a standard of truth that must be obeyed by their adherents. This is where the function of the teaching of social theology provides universal patterns for humans about the correct rules of the game, so as to create a religious society whose life is based on good morals, which will affect individuals who live and socialize in their environment, so that they become individuals who are personal. Social theology also answers the challenges of the times. As a result of the progress of science and technology has such a broad impact in various sectors of human life. These advances are found in communication technology. The role of social theology in this case is to filter out negative actions so that humans do not abandon their human values. Social theology teaches universal Hindu values. Where these values ​​make humans aware that we are all really brothers and sisters.